Advancing livestock systems: ILRI’s innovations and impacts in Southeast Asia - International Livestock Research Institute (International Livestock Research Institute, 2024)
Video produced in celebration of ILRI50 anniversary on 15 October 2024 in Hanoi, Vietnam.